Acute ethanol and taurine intake affect absolute alpha power in frontal cortex before and after exercise. (14th September 2017) - Paulucio, Dailson; da Costa, Bruno M.; Santos, Caleb G.; Velasques, Bruna; Ribeiro, Pedro; Gongora, Mariana; Cagy, Mauricio; Alvarenga, Renato L.; Pompeu, Fernando A.M.S.
Highlights: Taurine is used in the treatment of alcoholism and with ethanol through energy drinks. Little is known about the acute effects of taurine and possible modulations of mix with ethanol on cortical activity in frontal cortex. Ethanol reduces EEG activity, but this reduction is greater when taken with taurine. After exercise the EEG activity remains reduced in the taurine with ethanol treatment. Abstract: Taurine and alcohol has been popularly ingested through energy drinks. Reports from both compounds shows they are active on nervous system but little is known about the acute effect of these substances on the frontal cortex in an exercise approach. The aim of this study was to determine the effects of 0, 6 ml dL −1 of ethanol (ET), 6 g of taurine (TA), and taurine with ethanol (TA + ET) intake on absolute alpha power (AAP) in the frontal region, before and after exercise. Nine participants were recruited, five women (22 ± 3 years) and four men (26 ± 5 years), for a counterbalanced experimental design. For each treatment, the tests were performed considering three moments: "baseline", "peak" and "post-exercise". In the placebo treatment (PL), the frontal areas showed AAP decrease at the post-exercise. However, in the TA, AAP decreased at peak and increased at post-exercise. In the ET treatment, AAP increased at the peak moment for the left frontal electrodes. In the TA + ET treatment, an AAP increase was observed at peak, and it continued after exercise ended. These substances were able to produce electrocortical activity changes in the frontal regions after a short duration and low intensity exercise. Left and right regions showed different AAP dynamics during peak and post-exercise moments when treatments were compared.